Biogeochemical and Hydrological Variables Synergistically Influence Nitrate Variability in Coastal Deltaic Wetlands. Issue 9 (9th September 2021) - Sendrowski, Alicia; Castañeda‐Moya, Edward; Twilley, Robert; Passalacqua, Paola
Abstract: Coastal river deltas are centers of surface water nitrate processing, yet the mechanisms controlling spatio‐temporal patterns in nutrient variability are still little understood. Nitrate fluctuations in these systems are controlled by complex interactions between hydrological and biogeochemical drivers, which act together to transport and transform inorganic nutrients. Distinguishing the contributions of these drivers and identifying wetland zones where nitrate processing is occurring can be difficult, yet is critical to make assessments of nutrient removal capacity in deltaic wetlands. To address these issues, we analyze relationships among regional "external" (river discharge, tides, wind) and local "internal" (water level, temperature, turbidity, and nitrate) variables in a deltaic wetland in coastal Louisiana by coupling a process connectivity framework with information theory measures. We classify variable interactions according to whether they work uniquely, redundantly, or synergistically to influence nitrate dynamics and identify timescales of interaction. We find that external drivers work together to influence nitrate transport. Patterns of hydrological and sediment connectivity change over time due to tidal flushing and discharge variation. This connectivity influences the emergence of functional zones where local nitrate fluctuations and temperature and water level process couplings are strong controls on nitrate variability. High vegetation density decreases hydrological process connectivity, even during periods of high river discharge, but it also increases biogeochemical process connections, due to the lengthening of the hydraulic residence time. Based on these results we make recommendations for monitoring nitrate in a wetland. Plain Language Summary: With nitrate export to oceans expected to increase in the coming decades, river deltas will serve as an increasingly important site at continental margins for processing nitrate. It will be critical to understand the drivers of nitrate variability and identify locations of enhanced processing. We use information theory to quantify the process connectivity among regional hydrological and local biogeochemical controls on nitrate in a wetland in Louisiana. We find that river discharge fluctuations, tidal flushing, and vegetation density affect the hydrological connectivity of the wetland that governs the strength of hydrological and biogeochemical influences on nitrate. This study reveals the mechanisms that influence nitrate transport and transformation, which may be used to design monitoring studies and aid coastal restoration projects. Key Points: We measure how hydrological and biogeochemical controls influence nitrate fluctuations in delta wetlands by classifying variable interaction Wetland variables work together (act synergistically) to influence nitrate variability Nitrate variability is controlled by variation in vegetation density and external driver forcing